2021
DOI: 10.6007/ijarbss/v11-i12/11935
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analyses on the Vulnerability Types Suffered by Poor and Older Freshwater Fisheries Community Members in Peninsular Malaysia

Abstract: This paper aimed to measure the vulnerability type that predicts the likelihood of the respondents in poor category of household income by sex-disaggregated data. The respondents were sampled in Peninsular Malaysia (n=322)). They suffer from at least one out of six types of vulnerability asked in the questionnaire. HO1 (no type of vulnerability predicts male in poor category of household income), and HO2 (no type of vulnerability predicts male in poor category of household income) were tested through Binary Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…'no schooling/primary school' of academic background predicts MORW in the B40 household income category. This finding is supported bySaidi et al (2021) andZainalaludin (2012), who found that rural women are usually associated with low academic backgrounds and fisheries communities are in rural areas. Many studies also support this finding that fisheries community members have a common educational experience (William…”
mentioning
confidence: 60%
“…'no schooling/primary school' of academic background predicts MORW in the B40 household income category. This finding is supported bySaidi et al (2021) andZainalaludin (2012), who found that rural women are usually associated with low academic backgrounds and fisheries communities are in rural areas. Many studies also support this finding that fisheries community members have a common educational experience (William…”
mentioning
confidence: 60%
“…As women's life expectancy increases, they are also more likely to experience disadvantages in accessing education, food security, financial security, health care and social security compared to older men (Zainalaludin et al, 2020;Ismail et al, 2015;Chant, 2012). This means that older women are likely to be poor and face vulnerability and social disadvantage (Saidi et al, 2021;Zainalaludin et al, 2020). This is happening in Malaysia, which is currently experiencing a demographic shift among the elderly.…”
Section: Feminiszation Of Ageingmentioning
confidence: 99%
“…Many studies have found that older women are more likely to be poor (OECD, 2019;Ahmad et al, 2016;Siegenthaler, 1996), especially female heads of households (Masud et al, 2015). Many studies show older women have more disadvantages compared to older men (Tuohy & Cooney, 2019;Hamid, 2015) and yet they live longer than men, participate in household chores, and work for low wages or no payment (Saidi et al, 2021;Zainaludin et al, 2020;Ismail et al, 2015;Chant, 2012;Masud et al, 2008;Cox, 1998;Pearce, 1978). They deserve good life wellbeing towards last years of their lives, live happily and productive at their old ages.…”
Section: Feminisation Of Povertymentioning
confidence: 99%